Effectiveness and tolerability of formoterol plus glycopyrronium combination in patients with chronic obstructive pulmonary disease: FINE registry - Gopal, Bharat; Satish, K. S.; Garde, Samir; Sit, Niranjan Kumar; Kamdar, Dipali; Muchhala, Sameer; Jadhav, Ashwin V. (International Journal of Advances in Medicine, 2020)
Background: Long-term therapy for chronic obstructive pulmonary disease (COPD) is progressing fast. Dual bronchodilation with long-acting muscarinic antagonist (LAMA) and long-acting β2-agonist (LABA) fixed dose combinations (FDC) have been available over the past few years. To evaluate the real-world tolerability and effectiveness of formoterol plus glycopyrronium FDC inhaler, a post-marketing surveillance study was conducted in Indian population. Methods: This was an open-label, observational registry in which COPD patients, who were prescribed forglyn (a brand of FDC of glycopyrronium 25 mcg and formoterol fumarate dihydrate 6 mcg dry powder inhalation). The effectiveness, safety and tolerability of this LAMA/LABA combination were evaluated for 4, 8 and 12 weeks. The safety and tolerability was assessed based on the incidence of adverse events (AEs). Effectiveness was evaluated based on change in total symptom score from baseline to end of 12 weeks. The forced expiratory volume in 1 second (FEV1) was performed at baseline and end of 12 weeks. Results: Total COPD patients enrolled were 605, of which 78.5% were males and 21.5% were females. Patients showing improvement of symptoms at week 4 were 587 (97.02%). Overall, at the end of 8 week and 12 week 98.34 % and 99.49% patients showed improvement in the total symptoms respectively. About 0.49% did not show any improvement. AEs were reported in 64 (10.64%) patients with no serious AEs. Mean FEV1 of 476 patients before treatment was 1.53±0.68 L at baseline which changed to 1.85±4.74 L at the end of 12 weeks, with was statistically significant (p<0.05). Conclusions: In real-life clinical practice in India, formoterol and glycopyrronium FDC dry powder inhaler was well tolerated in COPD patients, and can be regarded as an effective option for maintenance treatment.